I Can’t Get No (Need) Satisfaction: Applying Basic Psychological Needs Theory to Foster Human Connection and Improve Applicant Reactions in Asynchronous Video Interviews. - Moore, Hayley Ina (Curtin University, 2023)
This research addresses the importance of making job applicants feel valued and respected, and tries to find ways to humanize high-stakes interactions in the digital age. In particular, this research experiments with designing one-way video interviews to increase applicants’ sense of connection to the hiring organization. The results underscore the need for organizations to develop these assessments with humane technology principles in mind, in order to foster positive reactions from applicants and secure top talent.